Impact of Trace Amounts of Sc and Zr on the Tribological Performance of Al-Bronze Against Stainless Steel Counterface in Varying Conditions - Mohammad Salim KAISER (Engineering Transactions, 2024)
The influence of trace amounts of scandium (Sc) and zirconium (Zr) on the tribological behavior of aluminum (Al)-bronze has been studied under ambient conditions in various t sliding environments, including dry conditions, fresh water, and simulated seawater. The findings demonstrate that trace amounts of Sc and Zr significantly influence wear properties, improving Al-bronze performance in dry sliding conditions while diminishing it in wet and corrosive environments. The addition of Sc and Zr refines the grains, increases the thermal stability of Al-bronze through intermetallic formation, and is simultaneously affected by oxidation and corrosion. Scandium increases the intensity of these effects, as intermetallic compounds strengthen the alloy but also accelerate the corrosion process.